METAKRITIK UNTUK SUBAGIO SASTROWARDOYO - Arif Bagus Prasetyo (POETIKA, 2013)
troke-width: 0px; "> AbstractSubagio Sastrowardoyo produces good structural analysis in a number of literary studies. One is the studyof Sitor Situmorang‘S poetry Sosok Pribadi dalam Sajak. The essay is submitted by Teeuw “as an example andvery precise topic” about endeavor of searching the hidden meanings in unanimity and elusive of modern poetry. InSitumorang‘s poetry , the focus discussion of Sastrowardoyo about literature and culture is based on a reading SosokPribadi dalam Sajak (SPdS), Sastra Hindia Belanda dan Kita, SHBdK dan Bakat Alam dan Intelektualisme.Overall, the SPDs are written which prioritizes the interpretation of the inner world , psychiatric or “private figure”author as depicted on the content of his work. Content, strong romantic and modernist understanding that puts the artistat the center of artistic creation, has encouraged Sastrowardoyo to blur quality of assessment and work of the authorpersonally, and to blur the distinction between art criticism and morality criticism, and the issue of aesthetics and ethicsmatters. Sharpness, accuracy, and diligence analysis are often dimmed by passion on doing “holy inquisition” against theauthor. In SHBdK, Sastrowardoyo shifts away from expressive to structural approach, though he never lost interest inthe “private figure” of the author.Keywords: meta-critic , Subagio, SPDs, aesthetics, ethics